2010 International Conference on Innovative Computing Technologies (ICICT) 2010
DOI: 10.1109/icinnovct.2010.5440086
|View full text |Cite
|
Sign up to set email alerts
|

A framework approach using CMMI for SPI to Indian SME'S

Abstract: Software developmentis carried out in different methods and using several standards.Software Process Improvisation (SPI) is the key for developing quality software. Software development companies are not only big organizations but there are many small settings usually called SME (Small and Medium Enterprises) or SMB (Small and Medium Business) which plays a major role in the software industry. CMMI model is applicable to small organizations also for process improvisation. The primary focus is to develop a fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…There are many different reasons, presented in the literature, why an SPI initiative succeeds or fails. Some researchers link the success of an SPI initiative to the organization size (e.g., large or SMEs) (Sánchez-Gordón et al, 2016) (Mutahar et al, 2016;Sivashankar et al, 2010). Others propose that some development processes improve the ability for successful SPI, e.g., SPI and agile methodologies (Chetankumar Patel, 2009;Polavarapu and Jami, 2016).…”
Section: Background and Related Workmentioning
confidence: 99%
“…There are many different reasons, presented in the literature, why an SPI initiative succeeds or fails. Some researchers link the success of an SPI initiative to the organization size (e.g., large or SMEs) (Sánchez-Gordón et al, 2016) (Mutahar et al, 2016;Sivashankar et al, 2010). Others propose that some development processes improve the ability for successful SPI, e.g., SPI and agile methodologies (Chetankumar Patel, 2009;Polavarapu and Jami, 2016).…”
Section: Background and Related Workmentioning
confidence: 99%
“…On the other way, there has been developed as result of research works models [9][17], methodologies [16], approaches [18][19] [20], methods [12], projects [21], frameworks [22] among others which pretend to help SMEs in the implementation of SPI initiatives.…”
Section: Software Process Improvement In Smesmentioning
confidence: 99%
“…In this regard, several software process improvement (SPI) models have been developed to improve software process development. For instance, the Capability Maturity Model Integration (CMMI) [4], SPICE [1,6], Bootstrap [5], International organization for standardization ISO 9000 [8,7], the Capability Maturity Model (CMM) [2,3,18], and Six Sigma [13]. These standards were developed in last decade to assist and help corporations to achieve more reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted in this context, the firms that use these standards showed excellent improvements in their development processes. For example, Hughes Aircraft adopted CMM standard in its development process and that enhanced its efficiency by saved millions of dollars [9].Unfortunately, some of earlier studies have been reported [1] [10] that all of these models are not applicable in software SME firms because they will face the problems of high cost to implement, time consuming, and resource constraints. Moreover, these standard models were developed to manage and improve the software development process in large and very large firms.…”
Section: Introductionmentioning
confidence: 99%